Protective effect of Yerba mate (Ilex paraguariensis St. Hill.) against oxidative damage in vitro in rat brain synaptosomal/mitochondrial P2 fractions. (July 2017) - de Lima, María Eduarda; Colpo, Ana C.; Maya-López, Marisol; Rosa, Hemerson; Túnez, Isaac; Galván-Arzate, Sonia; Santamaría, Abel; Folmer, Vanderlei
Highlights: Ilex paraguariensis extract and CGA are direct antioxidants capable of neutralizing ROS formation. Components of yerba mate extracts seem to act coordinately to exert antioxidant and protective effects. Yerba mate extracts can exert beneficial effects at the Central Nervous System level. Abstract: Yerba mate extracts are naturally enriched with several antioxidant compounds. Therefore, this natural product constitutes a fertile field of research directed to test its antioxidant and therapeutic properties in the Central Nervous System. We tested the ability of yerba mate to prevent the chemically-induced reactive oxygen species (ROS) formation, lipid peroxidation, glutathione balance (GSH:GSSG) disruption and mitochondrial dysfunction in vitro in rat brain synaptosomal/mitochondrial fractions, and compared these effects with those of its most abundant compound chlorogenic acid (CGA). Yerba mate prevented glutathione depletion and mitochondrial dysfunction, and these effects were correlated with its ability to prevent ROS formation. CGA prevented oxidative damage and mitochondrial dysfunction, but its effects were less intense than those of the extract. Our results suggest that the protective properties exhibited by yerba mate cannot be merely attributable to its main component CGA.